Water Pollution from the Activity of Large-Ruminant Animal Quarantine Installation (AQI) in Its Receiving Water Body - N. Zainuddin; M. S. Maarif; E. Riani; S. M. Noor (Tropical Animal Science Journal, 2019)
Indonesia governs the post-entry observation through the Animal Quarantine Installation (AQI) as a precautionary measure to minimize the risk of the entrance and the spread of animal infectious organism and disease of import animals. However, wastes generated from their activities are potentially pollute the environment. This research aimed to evaluate the pollution from AQI activity on its receiving water body. The study was conducted at 5 companies as follow: PT. A, PT. B, PT. C, PT. D, and PT. E. The samples were taken from their wastewater and the river where the waste was discarded with two replications. Direct measurement was carried out in the field by using water quality equipment to analyze pH, temperature, DO, and TDS. For other analysis, samples collected were preserved in refrigerator at 4 °C before laboratory testing was carried out to minimize microbiological decomposition of solids. Pollution variabels were analyzed by analysis of variance test (ANOVA) with 95% confidence level followed by turkey test. The results showed that there was no difference in pollution from temperature, DO, TDS, TSS, COD, and ammonia variables from 5 companies. In contrast, two variables i.e., pH and BOD indicating the difference among 5 companies (P<0.05). In conclusion, the results of wastewater variables from large-ruminant AQI activity were generally exceeding the Quality Standard of Wastewater for cattle-farming. Thus there is a pollution of water bodies in the environment around AQI due to their activities.